THE NUMBER OF WOMEN IN THE BOARD AND CORPORATE FINANCIAL PERFORMANCE IN CHINA - LIN, ZIQI (2019)
Incorporating more women into the board of directors is often regarded as a correct business decision, which breaks the traditional “glass ceiling” phenomenon. In general, senior managers believe that women directors in the board can provide unique insights on how an entity is perceived, thereby facilitating more open discussion among board members and improving the relationship between employees and board members. The purpose of this study was to explore whether gender differences in the board could improve the financial result of 1,589 A-share listed companies in China between 2013 and 2018. In this study, quantitative research method was adopted on the basis of secondary data collected from the official CSMAR database, which covered the board composition and the performance of the companies. Microsoft Excel and STATA 16.0 software were used to analyze the data through systematic review, so as to achieve the research objectives. The results demonstrated that gender differences can promote the financial performance of Chinese listed companies. The educational level of women directors is in direct proportion to the company’s financial performance. In addition, in China, if two women exist on the board, women as the minority have the greatest influence on the company. Therefore, public listed companies should put more attention on the right combination of men and women, instead of merely relying on the presence of no more than one woman to increase company performance. This study provides new insights into China’s board dynamics. Corporate performance should be measured both quantitatively and qualitatively in future research.